2016
DOI: 10.1007/s11136-016-1337-z
|View full text |Cite
|
Sign up to set email alerts
|

Deriving population norms for the AQoL-6D and AQoL-8D multi-attribute utility instruments from web-based data

Abstract: Post-stratification weights were used to ameliorate potential bias in the derivation of norms from web-based data for the AQoL-6D and AQoL-8D. The methods may be used generally to obtain norms when suitable auxiliary variables are available. The inclusion of an enlarged psycho-social component in the two instruments significantly alters the demographic profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
95
3
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 26 publications
7
95
3
2
Order By: Relevance
“…Even so over 12 months the patients' QOL scores remained relatively stable, and this result may have been due to adaptation to living with a low QOL, that is, a response shift in a person's perception that their QOL has become their new normal (Schwartz & Sprangers 1999). We found that the independent living sub-score was more than two standard deviations lower in this cohort than population norms (Maxwell et al 2016). This, in part, may be due to the overall median age of the cohort coupled with the typical complications and mobility dysfunction experienced by patients with advanced CKD (e.g.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Even so over 12 months the patients' QOL scores remained relatively stable, and this result may have been due to adaptation to living with a low QOL, that is, a response shift in a person's perception that their QOL has become their new normal (Schwartz & Sprangers 1999). We found that the independent living sub-score was more than two standard deviations lower in this cohort than population norms (Maxwell et al 2016). This, in part, may be due to the overall median age of the cohort coupled with the typical complications and mobility dysfunction experienced by patients with advanced CKD (e.g.…”
Section: Discussionmentioning
confidence: 62%
“…We found that the independent living sub‐score was more than two standard deviations lower in this cohort than population norms (Maxwell et al . ). This, in part, may be due to the overall median age of the cohort coupled with the typical complications and mobility dysfunction experienced by patients with advanced CKD (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…After 6 months, participants in both groups improved their ‘psycho‐social’ dimension score, P = 0.001; ‘physical’ dimension score, P = 0.03; and overall AQol8D score, P = 0.003, suggesting that neither diet had a detrimental effect on the quality of life. When compared to Australian males of similar age, this population group, on average, scored lower in all domains across all time points …”
Section: Resultsmentioning
confidence: 74%
“…When compared to Australian males of similar age, this population group, on average, scored lower in all domains across all time points. 15 There were no major adverse side effects experienced in either dietary group. Participants in both groups experienced only minor physical symptoms (see Table 2).…”
Section: Resultsmentioning
confidence: 85%
“…QoL assessment tools, such as the Assessment of Quality of Life scales may offer additional insight into patients' daily lives and provide a patient-centered measure of VA's efficacy when employed in future trials. 42 Different time point studies (length of follow-up) by each meta-analysis and the bias inherent in choosing which trials to include or exclude also contributes to this heterogeneity. In any case, more controlled trials are needed to conclude whether PVA can improve pain, function and QoL in patients suffering from VCFs.…”
Section: Limitationsmentioning
confidence: 99%